Evaluation of mobile health applications for cervical cancer in the digital marketplace - Jakkapop Kanjak; Naratassapol Likitdee; Chumnan Kietpeerakool; Amornrat Temtanakitpaisan (Korean Society of Obstetrics and Gynecology, 2022)
Objective To assess the quality of mobile health (mHealth) applications (apps) for cervical cancer using the mobile app rating scale (MARS), APPLICATIONS scoring system, and app rating using specific statements. Methods We searched for cervical cancer apps on two major mobile operating systems (Google Play Store and Apple iTunes Store) in March 2021. Eligible apps were downloaded and assessed for quality by two independent reviewers using multimodal assessment tools. Results The overall quality of the MARS score was 2.61±0.795. The highest scoring app was "The American Society for Colposcopy and Cervical Pathology (ASCCP) Management Guidelines" (3.98). Overall, apps scored highest in the functionality domain, followed by information, engagement, and aesthetics domains. The mean±standard deviation of the APPLICATIONS scoring system was 8.50±1.712. The highest-rated apps were "ASCCP Management Guidelines," "The British Society for Colposcopy and Cervical Pathology (BSCCP)," and "Cervical Cancer Guide." Apps scored the highest in the paid subscription and price domains. By contrast, apps scored poorly in the text search, literature, and subjective presentation domains. Concerning app content, many apps infrequently provided misconceptions regarding cervical cancer. The apps' rating using specific statements was 7.81±4.562. Conclusion Overall, the apps analyzed using the MARS and APPLICATIONS scoring systems demonstrated above-average quality. However, there is a need to improve the essential information conveyed by these applications. Moreover, the assessment tools have influenced different app quality rating results, confirming the lack of standardized quality assessment tools for mHealth apps.